Pharmacokinetic Assessment of Staphylococcal Phage K Following Parenteral and Intra-articular Administration in Rabbits - Totten, Katherine M.C.; Cunningham, Scott A.; Gades, Naomi M.; Etzioni, Athema; Patel, Robin (Frontiers in Pharmacology, 2022)
The therapeutic value of phage as an alternative to antibiotics for the treatment of bacterial infections is being considered in the wake of mounting antibiotic resistance. In this study, the pharmacokinetic properties of Staphylococcus aureus phage K following intravenous and intra-articular administration were investigated in a rabbit model. Using a traditional plaque assay and a novel quantitative PCR assay to measure phage levels in specimens over time, it was found that intra-articularly administered phage enters the systemic circulation; that phage may be detected in synovial fluid up to 24 h following the intra-articular, but not intravenous, administration; and that qPCR-based enumeration is generally more sensitive than plaque enumeration, with fair to moderate correlation between the two methods. Findings presented should inform the design of phage therapy experiments and therapeutic drug monitoring in preclinical and human phage studies.